Development of photocatalyst for CO2 conversion to hydrocarbon fuel - Nurul Izaaz, Azmi (2018)
Owing to the limited amount of energy sources and the recent effects of fossil fuel use on the global environment, the paradigm of energy supply is changing from one based on the use of carbon-rich rocks, peat, and liquid found in the Earth to one based on renewable sources, such as energy crops, sunlight, and wind. Several methods for reducing the carbon dioxide concentration in the atmosphere and preventing CO₂ emissions due to human activity have been investigated, such as investigating the sorption of CO₂ into new/functionalized materials; increasing the quantity of green carbon sinks (plants, phytoplankton, and algae containing chloroplasts); increasing the level of dissolved carbonate and its salts in sea water; or capturing CO₂ and transferring it to the bottom of the sea in a supercritical state. Photocatalytic reduction of CO₂ to fuels using solar energy is an attractive option for simultaneously capturing this major greenhouse gas and solving the shortage of sustainable energy. To conquer the problem of increasing CO₂ in the atmosphere, a solution using TiO₂ to convert CO₂ into usable fuel are conducted. Basically, the approach centres on the concept of the large-scale re-use of CO₂ released by human activity to produce synthetic fuels, and how this challenging approach could assume an important role in tackling the issue of global CO2 emissions. There are three main objectives of this research which are to design, synthesis and develop an efficient modified nano-based TiO₂ to enhance the reduction of CO₂ to fuel, methane (CH4) through photocatalyst, to study the material chemistry of modified Nano-based TiO₂ who enhance the process of the photocatalyst and to utilize the prepared photocatalyst for CO₂ conversion to CH4 in term to reduce greenhouse effect. The photocatalytic experiment conducted by synthesising TiO₂. Addition or doping with noble metal, such as platinum (Pt), palladium (Pd), silver (Ag) and gold (Au) ions allow extending the light absorption of band gap semiconductors to the visible light. Noble metals could be introduced to the surface of TiO₂ by various methods such as: electrolysis, chemical reduction, UV photoreduction, γ-reduction deposition from colloids or adsorption of metal clusters. The characterizations are 9 focused on optical and physical characterization. Then, the evaluation of photocatalyst process is carry out in a solid gas phase photoreactor. A tungsten – halogen lamp with high pass UV light filter are use as the visible light source. The CO₂ are bubbled through the water vapour into the chamber. The result is collected and analyse for the CH4 yield using gas chromatography system. The information gained from this analysis will help to contribute towards a better understanding of the main parameters that affect the activity of photocatalysts and will ultimately lead to the optimized synthesis of more efficient photocatalytic material for the photocatalytic reduction of CO₂ to hydrocarbon fuels.